3D Linear viscoelastic behaviour of bituminous mixtures containing high content of multi-recycled RAP. Issue 7 (3rd October 2019) - Pedraza, A.; Di Benedetto, H.; Sauzéat, C.; Pouget, S.
Abstract : This paper presents some results of a study on bituminous mixtures produced with high content of Reclaimed Asphalt Pavement (RAP), which is recycled several times. It deals with the linear viscoelastic (LVE) behaviour of the mixtures. This research is included in a project called IMPROVMURE, founded by the French National Research Agency (ANR). This article concerns six bituminous mixtures made in the laboratory. Among the six tested mixtures, three were hot bituminous mixtures and three were produced according to a warm process with foamed bitumen. For each one of the two processes, the reference mixture contains no RAP. The second mixture contains 70% RAP coming from the milling process. The third mixture was made with 70% of the second mixtures, aged artificially in the lab and recycled. Then, the third mixtures are made with materials recycled twice. Complex modulus E * and complex Poisson's ratio ν * were then measured for the six considered mixtures. The time-temperature superposition principle (TTSP) was verified. Experimental results were modelled using the Linear Viscoelastic (LVE) 2S2P1D (2 springs, 2 Parabolic Elements and 1 Dashpot) model in 3D. Fitted parameters of the model enable to compare the LVE behaviour of the three mixtures.